Current Situation of Scientific Research at the University of Jordan from the Viewpoint of Graduate Students - Atif Omar Bin Tareef; Ziad Ahmed Twissi (University of Science and Technology, Yemen, 2017)
This study aimed to identify the current status of scientific research at the University of Jordan as perceived by graduate students and the differences between students of science and humanities faculties, and to identify their opinions regarding ways to improve scientific research at the University of Jordan. The study followed a descriptive methodology based on a survey that was developed specifically for the purpose of this study. The survey consisted of 40 items covering 5 themes, and was distributed to a sample of 104 male and female participants representing science and humanities faculties. The data were analyzed, using the two-way ANOVA, the standard deviation and means. In addition, students' opinions and obstacles to effective participation of graduate students were categorized. The results showed significant differences between students' assessment of the status of scientific research in science and humanities faculties, which was (3.2) for students in humanities faculties and (2.8) for students in science faculties. The difference also appeared in all the five domains of the scientific research, while there was no presence of gender effect, neither was there effect for the interaction between the variables (gender and the faculty). The study recommended to provide financial support to scientific research, and to establish a refereed scientific Journal for publishing students' innovative ideas and research projects. Keywords: Scientific research, Graduate students.